2020
DOI: 10.1111/ceo.13797
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of different morphologies of choroidal neovascularization evaluated by ocular coherence tomography angiography in age‐related macular degeneration

Abstract: Importance: The clinical implications of different morphologies of choroidal neovascularization (CNV), as evaluated by ocular coherence tomography angiography (OCTA) in neovascular age-related macular degeneration (nAMD), are lacking. Background: To describe the morphology of CNV in nAMD using OCTA, and to compare the visual prognosis and other structural OCT biomarkers between different morphologic patterns. Design: Retrospective cohort study. Participants: One hundred and forty eyes with nAMD treated with an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 31 publications
3
6
0
Order By: Relevance
“…In the present study, 27.2% of eyes exhibited the Medusa pattern, 36.3% the seafan pattern, 22.7% the tangled pattern and 13.6% another pattern (i.e., ill-defined but measurable MNV). Consistent with Tew et al ( 16 ), there was a higher proportion of eyes with the seafan pattern in the present study ( 27 ).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In the present study, 27.2% of eyes exhibited the Medusa pattern, 36.3% the seafan pattern, 22.7% the tangled pattern and 13.6% another pattern (i.e., ill-defined but measurable MNV). Consistent with Tew et al ( 16 ), there was a higher proportion of eyes with the seafan pattern in the present study ( 27 ).…”
Section: Discussionsupporting
confidence: 93%
“…Tew et al ( 16 ) further differentiated and reported tangled pattern complexes with a main trunk or feeder vessel. In their study of 140 eyes, they identified MNV in 78.6%, with 37.3% displaying the Medusa pattern, 39.1% the seafan pattern and 23.6% the tangled pattern.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The MNV was further outlined using the “contour function” of the built‐in software, and the flow area was determined automatically (Figure S2). We calculated MNV vessel density (%) as the percentage of the measured area occupied by flow area 16 . En face OCT and OCTA of the deep choroid were obtained using manual adjustment, with the upper boundary aligned to the junction between Sattler's and Haller's layers, and the lower boundary aligned with the choroidal‐scleral interface.…”
Section: Methodsmentioning
confidence: 99%
“…Yang et al 12 show the value of ultra‐widefield imaging for detection of peripheral retinal lesions in high myopia before implantable collamer lens surgery. Tew et al 13 identify different patterns of choroidal neovascularisation in age‐related macular degeneration – with different visual prognoses – using OCT‐angiography.…”
mentioning
confidence: 99%